PENGARUH LAYANAN KONSELING INDIVIDUAL UNTUK MENINGKATKAN PERILAKU ASERTIF SISWA - Musuki Musuki; Dewi Yulianti; Halizatul Aini (Jurnal Bimbingan dan Konseling Borneo, 2023)
AbstractThe effect of individual counseling services to improve students' assertive behavior in class XI MA NW Senyiur 2020/2021 academic year. Thesis, a study program for guidance and counseling of the Faculty of Education (FIP) Hamzanwadi University. This study aims to determine the effect of individual counseling services to improve students' assertive behavior in class XI MA NW Senyiur 2020/2021 academic year. This type of research is an experiment with the A-B design research design. The subject of this research is a student in class XI. The data collection technique used an assertive behavior questionnaire and analyzed using quantitative data in the form of numbers which were processed using simple statistics. The results of this study indicate that the initial condition data before being given treatment (pretest) in the form of individual counseling services is in the low category with a score of 9 being vulnerable to 0 10 and the conditions after being given treatment (posttest) individual counseling services are in the high category with a score of 25 being vulnerable 20 30, and the scores on each aspect before being given individual counseling services are in the low category, namely the affective component aspect, the score is 30%, the cognitive component aspect is 37%, the conation component aspect is 25%, then after being given individual counseling services there is an increase In each aspect, the affective component aspect scored 80%, the cognitive component aspect was 87%, and the conation component aspect was 83%. This is in accordance with individual counseling, where there is a counseling relationship with report card nuances, and the counselor seeks to provide assistance for the counselee's personal development and the counselee can anticipate the problems they face. The researchers conclude that individual counseling can help the counselee's problem, namely the change from low assertive behavior to high assertive behavior.Keywords :Iindividual counseling service, assertive behaviorAbstractPengaruh layanan konseling individual untuk meningkatkan perilaku asertif siswa di kelas XI MA NW Senyiur Tahun Pelajaran 2020/2021. Skripsi, program studi bimbingan dan konseling Fakultas Ilmu Pedidikan (FIP) Universitas Hamzanwadi. Penelitian ini bertujuan untuk mengetahui pengaruh layanan konseling individual untuk meningkatkan perilaku asertif siswa di kelas XI MA NW Senyiur TahunPelajaran 2021/2022. Jenis penelitian ini adalah eksperimen dengan desain penelitian desain A-B. Subjek penelitian ini adalah seorang siswa yang kelas XI. Teknik pengumpulan data menggunakan angket perilaku asertif dan dianalisis menggunakan data kuantitatif berupa angka-angka yang diolah menggunakan statististik sederhana. Hasil penelitian ini menunjukkan bahwa data kondisi awal sebelum diberikan perlakuan (pretest) berupa layanan konseling individual berada pada kategori rendah dengan skor 9 berada pada rentan 0 10 dan kondisi setelah diberikan perlakuan (posttest) layanan konseling individual berada pada kategori tinggi denganskor 25 berada pada rentan 20 30, dan skor pada setiap aspek sebelum diberikan layanan konseling individual berada pada kategori rendah yaitu pada aspek komponen afektif skor sebesar 30%, aspek komponen kognitif 37%, aspek komponen konasi 25%, kemudian setelah diberikan layanan konseling individual terjadi peningkatan pada setiap aspek yaitu aspek komponen afektif skor sebesar 80%, aspek komponen kognitif 87%, dan aspek komponen konasi 83%. Hal ini sesuai dengan konseling individual adalah dimana terjadi hubungan konseling yang bernuansa raport, dan konselor berupaya memberikan bantuan untuk pengembangan pribadi konseli serta konseli dapat mengantisipasi masalah-masalah yang dihadapinya. Dapat peneliti simpulkan bahwa konseling individual dapat membantu masalah konseli yakni perubahan dari perilaku asertif rendah menjadi perilaku asertif tinggi.Kata Kunci : Layanan konseling individual, perilaku asertif